Shelf-Sourced Methane in Surface Seawater at the Eurasian Continental Slope (Arctic Ocean) - Vinogradova, Elena; Damm, Ellen; Pnyushkov, Andrey V.; Krumpen, Thomas; Ivanov, Vladimir V. (Frontiers in Environmental Science, 2022)
This study traces the pathways of dissolved methane at the Eurasian continental slope (ECS) and the Siberian shelf break based on data collected during the NABOS-II expedition in August-September, 2013. We focus on the sea ice-ocean interface during seasonal strong ice melt. Our analysis reveals a patchy pattern of methane supersaturation related to the atmospheric equilibrium. We argue that sea ice transports methane from the shelf and that ice melt is the process that causes the heterogeneous pattern of methane saturation in the Polar Mixed Layer (PML). We calculate the solubility capacity and find that seasonal warming of the PML reduces the CH4 storage capacity and contributes to methane supersaturation and potential sea-air flux in summer. Cooling in autumn enhances the solubility capacity in the PML once again. The shifts in the solubility capacity indicate the buffering capacity for seasonal storage of atmospheric and marine methane in the PML. We discuss specific pathways for marine methane and the storage capacity of the PML on the ECS as a sink/source for atmospheric methane and methane sources from the Siberian shelf. The potential sea-air flux of methane is calculated and intrusions of methane plumes from the PML into the Cold Halocline Layer are described.